The Influence of Tax, Institutional Ownership, and Profitability on Dividend Policy - Akhdan, Akhdan; Abdullah, Siti Intan Nurdiana Wong; Purwati, Astri Ayu (Research in Accounting Journal (RAJ), 2024)
This study investigates the impact of profitability, institutional ownership, and dividend policy on the firm value of Indonesian companies listed on the Indonesia Stock Exchange (IDX). Using a sample of companies from the manufacturing sector, the research examines how these financial variables influence the market value of firms. The study also explores the moderating role of tax planning and the relationship between dividend policies and firm profitability. The results indicate that profitability and institutional ownership have a significant positive effect on firm value, while dividend policy plays a crucial moderating role in enhancing firm value. Tax planning is also found to have a positive moderating effect on the relationship between profitability and firm value. These findings highlight the importance of maintaining a balance between profit distribution and retaining earnings for corporate growth. The study contributes to the broader understanding of corporate finance strategies, especially in emerging markets like Indonesia.